2003
DOI: 10.1248/cpb.51.409
|View full text |Cite
|
Sign up to set email alerts
|

1-Methyl-2-undecyl-4(1<i>H</i>)-quinolone as an Irreversible and Selective Inhibitor of Type B Monoamine Oxidase

Abstract: Monoamine oxidase (MAO; EC 1.4.3.4) is a flavin-containing enzyme that catalyzes the oxidation of a variety of amine-containing neurotransmitters such as catecholamines and serotonin to yield the corresponding aldehyde. [1][2][3] MAO exists in two isoforms, namely type A and type B (MAO-A and MAO-B), which are characterized by their sensitivity towards specific substrates and inhibitors. MAO-A preferentially deaminates serotonin and norepinephrine, and is selectively inhibited by clorgyline. However, MAO-B pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…310 1-Methyl-2-undecylquinolin-4(1 H )-one ( 165 ), an Evodia alkaloid, acted as an irreversible and selective inhibitor of type B monoamine oxidase. 311…”
Section: Bioactivities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…310 1-Methyl-2-undecylquinolin-4(1 H )-one ( 165 ), an Evodia alkaloid, acted as an irreversible and selective inhibitor of type B monoamine oxidase. 311…”
Section: Bioactivities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…Rather than PHF, the basal ganglia typically express high concentrations of aminergic projections, neuroreceptors, and their degrading enzymes such as monoamine oxidase (MAO) [4, 5]. As such, it is plausible to hypothesize that MAO-B (EC 1.4.3.4) constitutes a 18 F-THK5351 off-target binding site, particularly given its previous reported affinity to quinolone derivatives [6]. Furthermore, the presence of high concentrations of MAO-B in the human cortex demands a careful examination of the impact of MAO-B binding on 18 F-THK5351 images.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaloids are traditionally regarded as the major bioactive compounds in EF not only because a number of types of alkaloids were isolated from the herb,[121314] but also pharmacological and clinical studies indicated that alkaloids from EF had antipolysarcous,[15] cardiotonic,[1617] central stimulative,[18] vasodilatory,[1920] and anticancer activities. [212223] Evodiamine and rutaecarpine were specified as the biomarkers for quality assessment on EF in Chinese Pharmacopoeia (CP) (edition 2005),[24] and another compound, limonin, was used combined with evodiamine and rutaecarpine in CP (edition 2010)[1] for better assessment on this herb.…”
Section: Introductionmentioning
confidence: 99%